2007
DOI: 10.1590/s0034-76122007000300005
|View full text |Cite
|
Sign up to set email alerts
|

Consórcio de medicamentos no Paraná: análise de cobertura e custos

Abstract: A redução de custos na compra de medicamentos é preocupação constante dos administradores públicos. Este artigo analisa a cobertura e custos do Consórcio Paraná Saúde (CPS), constituído para aquisição de medicamentos para prefeituras do Paraná. A cobertura abrangeu os municípios participantes e suas populações. Os custos dos medicamentos adquiridos foram comparados com os valores constantes no Banco de Preços do Ministério da Saúde (BP/MS). Até o final de 2000, o CPS atingia 88,2% dos municípios e 55,6% da pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 1 publication
1
12
0
6
Order By: Relevance
“…Reports point out that well succeeded solutions for logistical and structural aspects are related to the protagonism of the state level and to a greater intermunicipal cooperation. Concerning medicines procurement, studies showed that the consortium system actually generates savings for the participant entities and greater supply stability (Amaral;Blatt, 2011;Ferraes;Cordoni Júnior, 2007). The role of the states seems to have been decisive in some successful cases of organizing and qualifying AFAB (Faleiros;Silva, 2014;Ferraes;Cordoni Júnior, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Reports point out that well succeeded solutions for logistical and structural aspects are related to the protagonism of the state level and to a greater intermunicipal cooperation. Concerning medicines procurement, studies showed that the consortium system actually generates savings for the participant entities and greater supply stability (Amaral;Blatt, 2011;Ferraes;Cordoni Júnior, 2007). The role of the states seems to have been decisive in some successful cases of organizing and qualifying AFAB (Faleiros;Silva, 2014;Ferraes;Cordoni Júnior, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…They tend to attract manufacturers who offer prices closer to production costs, with reduced cost per unit compared to retailers 9 , 11 , 18 . Associations or consortia of institutions for joint procurement also indicate that medicine prices are sensitive to economies of scale and negotiating power 1 , 5 .…”
Section: Discussionmentioning
confidence: 99%
“…5 In Paraná (southern Brazil) a consortium for medicines has been established, where municipalities unite to increase the scale of the purchase and negotiating power over prices. 5,7 These strategies were considered effective for the reduction of costs to acquire medicines.…”
Section: Discussionmentioning
confidence: 99%